2021
DOI: 10.3390/molecules26165049
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Characteristics of Bio-Oils and Their Utilization as Additives of Asphalts

Abstract: Transforming waste biomass materials into bio-oils in order to partially substitute petroleum asphalt can reduce environmental pollution and fossil energy consumption and has economic benefits. The characteristics of bio-oils and their utilization as additives of asphalts are the focus of this review. First, physicochemical properties of various bio-oils are characterized. Then, conventional, rheological, and chemical properties of bio-oil modified asphalt binders are synthetically reviewed, as well as road pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 72 publications
0
1
0
4
Order By: Relevance
“…Estudiosos analizaron al asfalto PEN 80/100 con adición de residuos de aceite de cocina en 0.2 y 3% determinando que el 2% era la dosis óptima obteniendo 95 de penetración a 25 °C, y al agregar 20, 40 y 60% de aceite de almendra de palma en la mezcla, sólo el 20% promovió la mejora logrando 98 a los 25 °C, siendo el 18.75% y 22.50% de mejora respectivamente [72].…”
Section: Grado De Penetraciónunclassified
“…Estudiosos analizaron al asfalto PEN 80/100 con adición de residuos de aceite de cocina en 0.2 y 3% determinando que el 2% era la dosis óptima obteniendo 95 de penetración a 25 °C, y al agregar 20, 40 y 60% de aceite de almendra de palma en la mezcla, sólo el 20% promovió la mejora logrando 98 a los 25 °C, siendo el 18.75% y 22.50% de mejora respectivamente [72].…”
Section: Grado De Penetraciónunclassified
“…Drugu značajnu grupu čine bio-ulja koja se dobijaju iz biomase biljnog porekla, koja se najčešće dobija kao nusproizvod poljoprivredne proizvodnje [15,16,17] i koja čini oko 60% svih izvora biomase [18].…”
Section: Tipovi Bio-vezivaunclassified
“…Postoji nekoliko tipova pirolize u zavisnosti od temperature i vremena zadržavanja, kao što su brza ili spora piroliza, karbonizacija ili gasifikacija. Za dobijanje bio-ulja se najčešće koristi brza piroliza zbog visoke efikasnosti, jednostavnosti i malih troškova [18].…”
Section: Postupci Dobijanja Bio-uljaunclassified
See 1 more Smart Citation
“…Bio-oils comprised of plant-based pyrolysis oils offer new potential as sustainable modifiers and partial replacements for petroleum-based asphalt [8]. Bio-oils contain lighter fluid fractions similar to maltenes in asphalt, which can supplement the asphalt's fluidity and improve workability and compactability [9]. Research has shown that bio-oils reduce the viscosity-temperature susceptibility of asphalt binders, enhancing performance at cold temperatures [10].…”
Section: Introductionmentioning
confidence: 99%